Phase Evolution in agsbs2 Thin Films Synthesized Via a Two-Stage Process - Radhalayam, D (Elsevier Ltd, 2025)
This study explores the influence of stacking order and sulfurization pressure on the phase evolution, structural properties, and optoelectronic performance of AgSbS2 thin films. Sulfurizing Sb/Ag and Ag/Sb/Ag stacks at 350°C revealed distinct outcomes: the Sb/Ag stack produced compact, phase-pure cubic AgSbS2 with a direct bandgap of 1.61 eV and high hole mobility (84 cm2V−1s2), while the Ag/Sb/Ag stack contained Ag3SbS3 impurities and exhibited reduced electrical performance. Sulfurization pressures from 750 Torr to 7.5 Torr significantly impacted crystallinity, phase composition, and grain morphology. Higher pressures favored phase-pure cubic AgSbS2 with enhanced compactness, while lower pressures promoted impurities and reduced film quality. The AgSbS2 solar cells fabricated from the Sb/Ag stack achieved 0.95% efficiency (VOC of 519.2 mV, JSC of 6.11 mA/cm2, FF of 30.0%), surpassing the efficiency of the Ag/Sb/Ag stack (0.7% efficiency, VOC of 513.4 mV, JSC of 4.45 mA/cm2, FF of 32.6%) due to improved phase purity. © 2025 The Authors